Analisis Penetrasi Sosial di Dunia Maya (Studi Peran Moderator di TikTok Live DJ Ronald) - Gunawan, Aloysius Bernanda; Sigit, Ridzki Rinanto (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
TikTok video sharing based social media is one of the most popular social media during the pandemic until now. TikTok facilitates the needs of its users to share and actualize themselves personally in mass media. This study aims to understand the stages of social penetration that can occur in online communities on TikTok Live and communities in the real world and the role of moderators in this stage. This research was conducted qualitatively by conducting observations and in-depth interviews with the parties in the community, namely content creators, moderators and audiences. The results of this study found that each party plays a different role in each stage of social penetration and can carry out acceleration and deceleration processes to speed up or slow down each stage for the benefit of the community. The findings of this study are expected to enrich the literature related to the theory of social penetration in cyberspace and the roles of the parties on TikTok.